2013
DOI: 10.1371/journal.pone.0067821
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Induction of Regulatory CD4+CD8α+ T Cells by TGF-β, IL-7 and IFN-γ

Abstract: In vitro CD4+ T cell differentiation systems have made important contributions to understanding the mechanisms underlying the differentiation of naive CD4+ T cells into effector cells with distinct biological functions. Mature CD4+ T cells expressing CD8αα homodimers are primarily found in the intestinal mucosa of men and mice, and to a lesser extent in other tissues such as peripheral blood. Although CD4+CD8α+ T cells are easily identified, very little is known about their development and immunological functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Mature T cells, expressing CD4 and CD8 coreceptors, have been observed in the periphery, hence, bringing into question the mutually exclusive expression of ThPOK and Runx3. Interestingly, when CD4/CD8a + DP T cells are generated in vitro by coculturing mature CD4 + T cells with TGF-b, IL-7, and IFN-g, Runx3 expression is increased, along with ThPOK being reduced [38], thus providing support for the idea that ThPOK and Runx3 expression may, in fact, be more plastic outside of the thymus in mature T cells than thought previously. In vivo, it was reported recently that mature CD4 + intraepithelial lymphocytes in the intestine concurrently express ThPOK and Runx3 [39].…”
Section: Origin Of Cd4/cd8 Dp T Cells In the Peripherymentioning
confidence: 66%
See 3 more Smart Citations
“…Mature T cells, expressing CD4 and CD8 coreceptors, have been observed in the periphery, hence, bringing into question the mutually exclusive expression of ThPOK and Runx3. Interestingly, when CD4/CD8a + DP T cells are generated in vitro by coculturing mature CD4 + T cells with TGF-b, IL-7, and IFN-g, Runx3 expression is increased, along with ThPOK being reduced [38], thus providing support for the idea that ThPOK and Runx3 expression may, in fact, be more plastic outside of the thymus in mature T cells than thought previously. In vivo, it was reported recently that mature CD4 + intraepithelial lymphocytes in the intestine concurrently express ThPOK and Runx3 [39].…”
Section: Origin Of Cd4/cd8 Dp T Cells In the Peripherymentioning
confidence: 66%
“…The underlying mechanism of this regulatory phenotype was IL-10 dependent, although the cells also expressed IFN-g but not IL-4. The ability of CD4/CD8 DP T cells to produce IL-10 and IFN-g but not IL-4 has been confirmed by another group, who likewise showed that mouse splenic CD4/CD8 DP T cells can exhibit a suppressive phenotype [38] and reduce T cell proliferation when cocultured with CD4 + T cells. In contrast, a study focusing on human skin biopsies from a GVHD patient reported the ability of CD4/CD8 DP T cells to produce IL-4 [37]; however, a possible regulatory function for these cells was upheld, based on their cytokine-secretion profile, which included IL-10, IFN-g, and TGF-b.…”
Section: Suppressive Potential Of Cd4/cd8 Dp T Cellsmentioning
confidence: 75%
See 2 more Smart Citations
“…4). In addition, some papers suggest that CD8αα can be transiently expressed 31,32 In some papers, CD4 -CD8α -TCRαβ + T cells are defined as DNT cells 33 . This fraction is not same as DNT cells in the current study, because considerable part of DNTs expresses CD8αα.…”
Section: Movie 6)mentioning
confidence: 99%